Association and linkage of DRD4 and DRD5 with attention deficit hyperactivity disorder (ADHD) in a sample of Turkish children - (:unkn) unknown (NATURE PUBLISHING GROUP, 2000)
The search for genetic factors predisposing to Attention Deficit Hyperactivity Disorder (ADHD) has focused on genes that regulate dopaminergic pathways such as dopamine receptors and enzymes that regulate levels of dopamine in the synapse. There have been several reports of association between ADHD and polymorphic variants within or near DRD4, DRD5, DAT1, DBH and COMT, in this study we set out to investigate specific alleles of DRD4 and DRD5, previously reported to be associated with ADHD, in a sample of Turkish children with DSM-IV ADHD children, as well as their relation to methylphenidate response and dimensional measures of symptom domains. One hundred and four independent trios and seven dyads were analysed using the transmission disequilibrium test (TDT), We found increased transmission of the DRD4 7-repeat allele (DRD4*7) (TDT chi(2) = 2.79, P = 0.047), Given that we were testing specific a priori hypotheses regarding the associated alleles, we have used one-tailed P values throughout. There was evidence of an interaction with methlyphenidate (MPH) response and analysis of the sample excluding non-responders revealed more significant evidence for the association (TDT chi(2) = 4.48, P = 0.017). We also detected a trend for linkage and association in the DRD5 polymorphism (TDT chi(2) = 2.38, P = 0.06), Similar findings were obtained in relation to MPH response as analysis of MPH responders alone gave rise to a more significant association than that of the group as a whole (TDT chi(2) = 4.9, P = 0.013), t-Test and logistic regression TDT analyses of DRD4*7 transmission with respect to dimensional rating scales of hyperactivity and impulsivity showed an inverse relation suggesting that in this sample DRD4*7 is associated with a lower level of ADHD symptomatology, While this may be due to stratification along a dimension of severity such that severe cases belong to a more extreme group with other specific genetic and environmental causes, similar to the model for low cognitive ability, it is more likely the result of a chance selection bias in this sample.
Keywords: linkage and association; dopamine D4 receptor gene (DRD4); dopamine D5 receptor gene (DRD5); attention deficit hyperactivity disorder (ADHD); CANDIDATE-GENE ASSOCIATION; DOPAMINE TRANSPORTER GENE; MINIMAL BRAIN-DYSFUNCTION; RECEPTOR GENE; RISK-FACTORS; DEFICIT/HYPERACTIVITY DISORDER; BIPOLAR DISORDER; NOVELTY SEEKING; POLYMORPHISM; SCHIZOPHRENIA